The effect of addition of calcium oxide (CaO) on the cultivation of Litopenaeus vannamei in freshwater - Husnul Ayu Juniarti; Nanda Diniarti; Andre Rachmat Scrabra (IJOTA (Indonesian Journal of Tropical Aquatic), 2022)
Indonesia, as the fourth-largest global producer of Vannamei shrimp, is facing increasing demand for shrimp, necessitating higher production. In response, the cultivation of Vannamei shrimp in freshwater has gained traction. However, freshwater environments are limited in essential calcium minerals required for shrimp growth. To address this issue, research on the addition of calcium oxide (CaO) in freshwater Vannamei shrimp cultivation was conducted. The main objective of this study was to assess the impact of calcium oxide (CaO) and determine the optimal dosage for the survival rate and growth of Vannamei shrimp in freshwater. The experimental method was employed, consisting of five different dosage treatments: seawater control, freshwater control, 40 ppm, 80 ppm, and 120 ppm of calcium oxide. The findings of this study revealed that the treatment with 120 ppm of calcium oxide exhibited the most favorable growth, with a weight of 16.40 g in the freshwater treatment. Additionally, the 80 ppm treatment demonstrated the highest survival rate, reaching 67% in the freshwater treatment.